GENETIC LITERACY IN ADOLESCENTS WITH GENETIC DISORDERS: A BIOPSYCHOSOCIAL AND CLINICAL APPROACH - Vargas-Vera, Ramón Miguel; Mejía-Gavilánez, Piedad Gisela; Placencia-Ibadango, Martha; Alencastro-Placencia, Saúl Alexander; Gunsha-Aguilar, Jorge Luis; Tipán-Hidalgo, Andrea Jimena; Lino-Mejía, Melanie Nicole; Silva, Karen Soraya Vargas (Seven Editora, 2026)
Genetic literacy constitutes an essential component in contemporary medicine, particularly in the management of adolescents with genetic disorders. This population group faces complex challenges encompassing biomedical, psychological, and social dimensions. The aim of this chapter is to analyze the role of genetic literacy in adolescents with genetic diseases, its relationship with psychological adaptation, and its clinical implications. The components of genetic literacy, associated factors, empirical evidence, and the role of genetic counseling are reviewed. Evidence suggests that, although levels of genetic literacy are often low, adolescents may present adequate levels of psychological adaptation, indicating the influence of psychosocial factors. An integrative biopsychosocial model is proposed to optimize clinical and educational interventions.